Features of lethal cases in patients with TB/HIV co-infection depending on the resistance to antituberculosis agents in the conditions of the antituberculosis dispensary - Sahaidak, Т. К.; Skorokhodova, N. О.; Akhtyrskyi, О. І.; Fedorets, А. V.; Yanovskyi, А. V. (Modern medical technology, 2019)
Purpose of the study. Analyze lethal cases in patients with the TB/HIV co-infection depending in resistance to anti-TB drugs in the conditions of the antituberculosis dispensary. Materials and methods. Retrospective analysis was conducted 80 histories and autopsy reports of patients with TB /HIV infection who died in the MI «Zaporizhzhya Regional Anti Tuberculosis Clinical Dispensary» from 2012–2017. Results. In patients with chemoresistant forms, disseminated tuberculosis was in 36 patients (90%), infiltrative tuberculosis was noted in 2 cases, focal and fibrosis and cavernous – one person each. In the disseminated processes, in addition to the lungs, intranuclear lymph nodes were more often affected – 19 (47,5%), meningoencephalitis – 9 (22,5%), pleurisy – 9 (22,5%), retroperitoneal lymphnodes 2 (5,0%), peripheral lymphnodes – 2 (5,0%), lesions of the spleen – 2 (5,0%), kidneys – 2 (5,0), intestine – 1 (2,5%). In patients with susceptible tuberculosis, pulmonary and extrapulmonary lymph nodes are found in 36 (90.0%), only extrapulmonary – 4 (10,0%). These were pulmonary disseminated processes, including miliary forms. In addition to the lungs, intrathoracic lymph nodes were more often affected in 16 patients (40,0%), in 14 (35,0%) cases there was TB meningoencephalitis, Objective mesenteric lymphnodes – 4 (10,0%), spleen – 3 (7,5%), kidneys – 3 (7,5%), liver – 3 (7,5%), brain tuberculoma –1(2,5%). Conclusions. Inconducting a comparative analysis of clinical and pathoanatomical diagnoses in patients with susceptible tuberculosis there was only one case in which a patient with brain tuberculoma had not been diagnosed with purulentnecrotizing pneumonia of the upper lobe of the right lung. In patients with resistant forms of tuberculosis in all cases there was a coincidence of diagnoses. The main secondary diagnosis was cryptococcal meningoencephalitis – 8 (20,0%), oncopathology – 2 (5,0%).